Preliminary Modeling of Transfer RNA Kinetics in the Cytoplasm of Escherichia coli Bacteria - Piros, Sandor (2010)
Transfer RNAs (tRNAs) can recognize a specific amino acid from a possible pool of 20. Theyare able to transport these protein building-blocks to the ribosome, the site where amino acids assemble into protein chains. Accurate and rapid selection of tRNAs bythe ribosome is critical for cell survival. The aim of this paper is to develop a preliminaryand simple model of tRNA molecular movement in the bacterial (Escherichia coli—E. coli) cytoplasm. We examine the spatial movement/placement of aminoacylated tRNAs in the cytoplasm—viewed from the perspective of that particular aminoacylated tRNA. To achieve this goal, a kinetic model of the interaction between messenger RNA, ribosome, and RNA molecules is developed. The purpose of the simulation is to examine the conditions necessaryf or the tRNA to deliver a particular amino acid to the ribosome within a biological timeframe. Simulation results show that it is unlikelythat tRNAs are able to reach the “A site” of the ribosome byr andom movement.